"ANALISIS KEMAMPUAN LITERASI DAN NUMERASI SISWA DALAM MENYELESAIKAN SOAL AKM KELAS V UPT SPF SD INPRES MARISO I - Nur Asmi; Andi Syukri Syamsuri, Maria Ulviani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to analyze the literacy and numeracy abilities of fifth-grade students at UPT SPF SD Inpres Mariso I in completing Minimum Competency Assessment (AKM) problems. This study employs a descriptive qualitative approach using non-interactive methods through document analysis. Data were collected through AKM tests, questionnaires, interviews, observations, and documentation. The findings indicate that most students have moderate literacy skills, being able to comprehend explicit information but struggling with critical analysis of texts. In terms of numeracy, students showed low performance, particularly in solving real-life contextual problems. A correlation was found between literacy and numeracy abilities, suggesting that students with stronger literacy skills tended to perform better in text-based numeracy problems. Factors affecting student performance include lack of AKM practice, non-contextual learning methods, low motivation, and limited learning resources.